Collaborative Virtual Learning Environments: A Structure for Designing Digital Educational Materials - Shuce Zhao (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Collaborative learning (CL) is primarily conducted in-person meetings these days. It is explained in more detail by identifying key aspects and benefits. Furthermore, social dimensions of learning are discussed, with an emphasis on communication and interaction. Therefore, the theoretical underpinning of educational environments is shared learning. An overview of virtual learning communities and prerequisites for participation are provided. This paper’s goal is to offer a few pieces of research on students and cooperative learning in virtual environments. Educations on cooperative learners in virtual environments are beginning to appear and will become more important, especially in online and remote learning contexts. It will be argued that virtual worlds’ layout and functioning offer a collaborative platform, especially for students who may have grown accustomed to and even prefer digitalized learning environments. Additionally presented is the environment’s design. This environment has been assessed using a hybrid evaluation methodology to identify usability challenges, gather additional requirements for new functionality to facilitate collaborative virtual learning environments, and assess the suitability of various learning scenarios.